2020
DOI: 10.1111/cod.13448
|View full text |Cite
|
Sign up to set email alerts
|

Hand eczema treatment: Change behaviour with text messaging, a randomized trial

Abstract: Background: Irritant contact dermatitis is the most common type of hand eczema.Effective treatment usually involves avoidance of irritants and use of appropriate topical medication. In this study, the effectiveness of using text messaging addressing preventive behaviours and appropriate medication adherence was evaluated. Methods: Patients who were admitted to Istanbul Training and Research HospitalDermatology Department March 1, 2015 to July 31, 2015, and diagnosed with hand eczema were enrolled. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Several studies indicated a diagnosis by a clinician as a requirement for inclusion ( 43 , 50 , 57 ). Other studies specified people with a ‘diagnosis’ as an inclusion criterion but failed to clarify whether this was a self- or clinician-diagnosis ( 40 , 45 47 , 51 , 55 , 56 , 58 61 ). However, given that research participants were mostly recruited from outpatient dermatology clinics ( 40 42 , 44 46 , 54 , 55 , 61 , 62 ) or using a combination of recruitment methods ( 52 , 53 , 58 60 ), it is reasonable to assume that most studies included people with an established dermatological condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicated a diagnosis by a clinician as a requirement for inclusion ( 43 , 50 , 57 ). Other studies specified people with a ‘diagnosis’ as an inclusion criterion but failed to clarify whether this was a self- or clinician-diagnosis ( 40 , 45 47 , 51 , 55 , 56 , 58 61 ). However, given that research participants were mostly recruited from outpatient dermatology clinics ( 40 42 , 44 46 , 54 , 55 , 61 , 62 ) or using a combination of recruitment methods ( 52 , 53 , 58 60 ), it is reasonable to assume that most studies included people with an established dermatological condition.…”
Section: Resultsmentioning
confidence: 99%
“…The three studies (41,45,46) that assessed knowledge all reported significant improvements. One study found a significant improvement (p = 0.007) in the average knowledge scores between intervention (11/14) and control (9/14) groups immediately post-intervention (46).…”
Section: Knowledgementioning
confidence: 98%
“…Probably, continuous encouragement by text messaging (for example SMS/whats app) could increase the use of topical and oral medication in future hand eczema care. 45 Chapter 7 confirmed that systemic treatments could reduce severity and, as a result, health-related quality of life, treatment satisfaction, and treatment adherence. This finding suggests that clinicians should probably intensify anti-inflammatory treatment sooner in cases of severe chronic hand eczema with its significant impact on HRQoL due, for example, to absenteeism and/or depression.…”
Section: Burdenmentioning
confidence: 82%
“…An independent association of FLG mutations and hand eczema has not been found. [44][45][46][47] Furthermore, independently of gene mutations, studies in atopic dermatitis showed lower expression levels of filaggrin, involurin, and loricrin due to proinflammatory cytokines as IL-4. 48,49 Both FLG mutations and decreased fillagrin expression were not found in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation